2020
DOI: 10.3389/fmicb.2019.03013
|View full text |Cite
|
Sign up to set email alerts
|

Endophytic Fungi of Native Salvia abrotanoides Plants Reveal High Taxonomic Diversity and Unique Profiles of Secondary Metabolites

Abstract: Endophytic fungi are often embedded in their host's metabolic networks, which can result in alterations of metabolite production and higher amounts of active compounds in medicinal plants. This study reports the occurrence, diversity, and secondary metabolite profiles of endophytic fungi isolated from Salvia abrotanoides plants obtained from three geographically distinct sites in Iran. A total of 56 endophytic fungi were isolated from roots and leaves of S. abrotanoides; site-specificity and root-dominated col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 64 publications
0
29
0
Order By: Relevance
“…1. However, a total of 56 endophytic fungi was isolated from leave and root segments of Salvia abrotanoides at the three sites by Teimoori-Boghsani et al [25]. The isolated strains belong to 16 different fungal genera, this including: Penicillium, Paraphoma, Phaeoacremonium, Talaromyces, Aspergillus, Psathyrella, Trichoderma, Alternaria, Thielavia, Acremonium, Fusarium, Talaromyces, Coniolariella, Paecilomyces, Simplicillium, and Monocillium.…”
Section: Endophytic Microorganism: Bacteria and Fungimentioning
confidence: 99%
“…1. However, a total of 56 endophytic fungi was isolated from leave and root segments of Salvia abrotanoides at the three sites by Teimoori-Boghsani et al [25]. The isolated strains belong to 16 different fungal genera, this including: Penicillium, Paraphoma, Phaeoacremonium, Talaromyces, Aspergillus, Psathyrella, Trichoderma, Alternaria, Thielavia, Acremonium, Fusarium, Talaromyces, Coniolariella, Paecilomyces, Simplicillium, and Monocillium.…”
Section: Endophytic Microorganism: Bacteria and Fungimentioning
confidence: 99%
“…Troncoso et al (2010) and Vergara et al (2018) also reported that the endophytic fungi F. subglutinans and DSSM were the predominant fungi among the endophytic fungal populations in the plant mycobiome with unique biologically active substances that do not cause any signs of diseases; these results are in line with our findings. Similarly, Teimoori-Boghsani et al (2020) reported that fungal endophytes of wheat proved to be promising biological control agents and offer an alternative safe strategy to wheat disease management. Fungal endophytes adapt particularly well to their host plant, colonize the same ecological niches as those of phytopathogens, and produce a wide range of secondary metabolites necessary for their survival and for the protection of their host against many phytopathogens and insect herbivores.…”
Section: Biological Control Activity Of the Endophytic Fungi Of Healthy T Aestivum Against The Phytopathogenic Fungi Of Wheatmentioning
confidence: 99%
“…Both DSSM and F. subglutinans are unique sources of bioactive substances such as salicylic acid, jasmonic acid, subglutinol A and B, gibberellin, and gibberellin oxidase that have been reported to regulate defense hormone signaling networks in plants and enhance resistance against pathogens and insect attack (Troncoso et al, 2010;Gong et al, 2012, Ozan, 2019Teimoori-Boghsani et al, 2020).…”
Section: Efficiency Of Seed Coating Treatments With the Selected Endophytic Fungi Against Root Rot Pathogensmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, considerable evidence indicated endophytic associations to be important for the plant immune system (Soliman et al, 2015), disease suppression (Terhonen et al, 2016), nutrient acquisition (Hiruma et al, 2016), plant fitness (Khare et al, 2018) and tolerance to abiotic stresses (Chagas et al, 2018;Shahzad et al, 2017;Silva, 2017). Many endophytes are known to be an important source of secondary metabolites and plant hormones (Hardoim et al, 2015;Muria-Gonzalez et al, 2015;Teimoori-Boghsani et al, 2020) and have the potential to synthesize various bioactive metabolites that may be used as therapeutic agents against numerous diseases (Aharwal et al, 2016;Duan et al, 2019).…”
Section: Introductionmentioning
confidence: 99%